Catastrophising, pain self‐efficacy and acceptance in patients with Burning Mouth Syndrome. (5th January 2021) - Chana, Pavneet; Smith, Jared G.; Karamat, Aalia; Simpson, Anna; Renton, Tara
Abstract: Background: Little is known about pain catastrophising, pain self‐efficacy and chronic pain acceptance in burning mouth syndrome (BMS) and their effect on health‐related quality of life (HRQoL) and symptoms of anxiety and depressive disorders. Objectives: To describe pain catastrophising, pain self‐efficacy and pain acceptance in BMS patients and explore associations with affective function and HRQoL. Methods: A cross‐sectional study of 36 BMS patients (31 female) referred to an Orofacial Pain Clinic completed the Pain Catastrophizing Scale, the Pain Self‐Efficacy Questionnaire and the Chronic Pain Acceptance Questionnaire‐8 in addition to standardised self‐reported questionnaires measuring mood and oral and generic HRQoL. Results: Pain catastrophising levels were markedly higher than (non‐clinical) population norms, with 32.0% of patients reporting clinically relevant levels. Pain self‐efficacy and chronic pain acceptance varied widely; 24.0% evidenced low confidence to cope with pain, and 53.8% reported low activity engagement and/or low pain willingness. Catastrophising showed moderate‐to‐strong associations with measures of anxiety ( r = 0.63), depression ( r = 0.80), and oral ( r = 0.61) and generic HRQoL ( rho =−0.84). Self‐efficacy and acceptance were also closely related to levels of depression ( r/rho =−0.83 to −0.73) and generic HRQoL ( r/rho = 0.74 to 0.75). These associations were stronger than those between pain severity and affective function/HRQoL and persisted after controlling for pain severity. Conclusions: A substantial proportion of BMS patients evidence maladaptive beliefs about personal effectiveness in managing pain, which is closely related to affective disorders and impaired HRQoL. As such, treatment approaches targeting catastrophising, pain self‐efficacy and acceptance may prove beneficial in improving mood and quality of life in BMS patients.